An Examination of the Influence of Veteran Status on Offense Type Among an Inmate Sample - Van Dyke, Kellie (American journal of criminal justice, 2017)
The current study examines the relationship between military service and criminal behavior of veterans, both combat and non-combat, compared to non-veterans using a nationally representative sample of inmates. Specifically, this study examines the relationship between veteran status and crime type among inmates in state and federal institutions. While the relationship between military service and criminal behavior of veterans has received considerable attention, many have failed to differentiate between veterans who have seen combat versus those who have not. Therefore, a subsample of veterans who experienced combat during their military service is examined to better inform our understanding how combat experience might influence this relationship. Multiple counterfactual methods, including propensity score matching, were used on data from the Survey of Inmates in State and Federal Correctional Facilities, 2004. Some significant differences exist in the types of offenses committed based on veteran status and combat experience, but in some cases contrary to expectations. Veterans were more likely to have committed a violent offense, but less likely to have committed drug offenses; whereas, combat veterans were more likely to commit a drug offense and less likely to commit a violent offense than non-combat veterans. Policy implications and recommendations for future research are explored.